Developing HOT Project-Based-Speaking Assessment to Stimulate the Students’ Critical Thinking and Creativity - Setiawan, Anjar; Linggar Bharati, Dwi Anggani (Universitas Negeri Semarang, 2018)
Most of English teachers do not comprehend how to construct items and develop High Order Thinking (HOT) project-based-speaking assessment to stimulate the students’ critical thinking and creativity. Therefore, this study is conducted to develop project-based-speaking assessment to stimulate the students’ critical thinking and creativity in English learning. This study uses research and development (R & D) at X IPA 1 of SMA N 15 Semarang. The data are gathered through interview, questionnaire, and observation which are aimed to know the existing of the implementation of HOT project assessment. Meanwhile, the data from pre-test and post-test are mini-drama performance to measure the students’ learning achievement. During the implementation of assessment, the students prepare the concept and perform mini-drama performance. The results indicate that the implementation of project-based-speaking assessment successfully stimulate the students’ critical thinking and creativity in English learning. Further, the results also show the students’ scores improvement of pre-test and post-test where the speaking skill is 70.11 to 82.11, the critical thinking is 60.69 to 87.50, and the creativity is 62.08 to 85.83. Moreover, the students participate in the process of teaching and learning actively. They are able to work in a group discussion to write the drama script and arrange the concept of drama cooperatively. Finally, they can perform the drama performance successfully. In conclusion, the HOT project-based-speaking assessment is applicable to stimulate the students’ critical thinking and creativity in English learning.